Komunikasi Persuasif dan Word of Mouth dalam Pemasaran Tabungan Haji Panin Dubai Syariah Bank - Perkasa Hamudya, Topan; Swarnawati, Aminah (Journal of Comprehensive Science, 2024)
Marketing communication has the function of conveying information, persuading and reminding potential consumers of products and services for making purchasing decisions. The type of product, the target market for prospective consumers, the strength of the network owned and the company's ability in terms of promotion budget are aspects that need to be considered in determining the form and channel of marketing communication for a product. Persuasive communication plays an important role for the company's success in influencing prospective customers to respond and act according to what is expected in relation to product marketing. Word of mouth about the experiences of customers who have enjoyed the company's products and services forms word of mouth which is an effective communication medium in influencing the decision making of other prospective customers. This study uses a qualitative approach and is descriptive in nature, aims to describe and analyze the application of persuasive communication elements and word of mouth elements as a form and channel of marketing communication for Hajj Savings at Panin Dubai Syariah Bank. The data used in this study are primary and secondary data. Primary data was obtained from direct observation and interviews, while secondary data was obtained from the results of research that had been carried out by previous researchers and scientific reports contained in articles or journals regarding persuasive communication and word of mouth. The results of the study show that the elements of persuasive communication (claims, warrants and data) are implemented in verbal communication by the opinion leaders and non-verbally in the choice of media sentences to promote PDSB Hajj Savings products. Word of mouth elements (WoM Units, Participants, Venues, Actions and Outcomes) occur and are implemented in the interaction process both by opinion leaders to the community and Hajj Savings customers who have experienced PDSB Hajj Savings services to the surrounding community.